(untitled) (Global Journal of Medical Research, 2022)
In the Introduction the topics dealt with in the previous work 1 are addressed which are again considered for the highlighted reflections Of the considerations concerning genetic groups two deserve to be highlighted The first is related to the emt group that contains an electron and the muon and tau neutrinos its relevance due to the fact that researchers have reported the existence of ghost particles that always appear together with electrons and that these ghost particles are the neutrinos Mentioned above of muon and tau The author believes that this genetic group has some connection with light